Cooperation in traffic routing games on scale free wireless networks - Dávid Csercsik (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
Local routing protocols in scale free networks have been extensively studied. In this paper we consider a wireless contextualization of this routing problem and analyze on the one hand how cooperation affects network efficiency, and on the other hand the stability of cooperation structures. Cooperation is interpreted as local exchange of topological information between cooperating agents, and the payoff of a certain node is defined based on its energy consumption during the routing process. We show that if the payoff of the nodes is the energy saving compared to the all-singleton case, basically coalitions are not stable. We introduce coalitional load balancing and net reward to enhance coalitional stability and thus the more efficient operation of the network. As in the proposed model cooperation strongly affects routing dynamics of the network, externalities will arise and the game is defined in a partition function form.
Keywords: C71; L14; L96; 330; partition function form games; networks; local routing